The ECB's enhanced effective exchange rates and harmonised competitiveness indicators: An updated weighting scheme including trade in services - Martin Schmitz; Andreas Dietrich; Rémy Brisson (European Central Bank (ECB), 2024)
The nominal effective exchange rate (EER) of a currency is an index of the tradeweighted average of its bilateral exchange rates vis-à-vis the currencies of selected trading partners, while the real EER is derived by adjusting the nominal index for relative prices or costs. The nominal EER provides a summary measure of a currency's external value, while the real EER is the most commonly used indicator of the international price and cost competitiveness of an economy. Additionally, for all individual euro area countries, harmonised competitiveness indicators (HCIs) are published by the European Central Bank (ECB) based on the same methodology as the euro EERs. This paper describes how the calculation of the ECB's EERs and HCIs has been enhanced to take into account in the underlying trade weights the evolution of international trade linkages and, in particular, the growing importance of trade in services. The paper includes an in-depth description of the methodology used to calculate these enhanced EERs and HCIs. In particular, it presents how to overcome the challenges arising from the inclusion of services trade, foremost in terms of data availability, with imputation and estimation techniques. Importantly, the ECB's wellestablished methodology - which in particular accounts for competition faced by euro area exporters in third markets - did not have to be changed with the inclusion of services trade. Finally, the paper provides some evidence on the usefulness of the enhanced indicators for policymakers, economic analysts and the public at large.
Keywords: C82; F10; F17; F30; F31; F40; 330; competitiveness; effective exchange rate (EER); harmonised competitiveness indicator (HCI); nominal effective exchange rate (NEER); real effective exchange rate (REER); services trade; trade weights; gravity model